A rare case of bowel perforation in an adult with antithyroid medication induced neutropaenic enterocolitis - Yuen, Alexander (International Surgery Journal, 2024)
Neutropaenic enterocolitis (NE) is a life-threatening complication of neutropenia rarely seen in adults. Cases of NE arising outside the context of haematological malignancies or oncological treatments remain extremely infrequent. We present a case of bowel perforation secondary to NE in a female adult patient who developed agranulocytosis after commencement of thionamide antithyroid medications for hyperthyroidism. Patients recently commenced on thionamides should be educated on the symptoms of agranulocytosis and present to the hospital. Emergency physicians and surgeons alike should have a high index of suspicion for NE in this group of patients and prompt surgical intervention may be required to reduce the significant mortality rate.